Longitudinal course of depression symptoms in multiple sclerosis - Arnett, P A (BMJ Group, 2006)
BACKGROUND: Despite the high lifetime prevalence of depression in multiple sclerosis (MS), its longitudinal course is poorly understood. OBJECTIVE: To examine the longitudinal course of and reliable change in different depression symptom clusters in MS, and the longitudinal association of interferon beta treatment and coping with depression symptoms. METHODS: 53 MS patients were examined at two time points three years apart on the Beck Depression Inventory (BDI) and the Chicago Multiscale Depression Inventory (CMDI). RESULTS: Correlations from time 1 to time 2 for BDI, CMDI‐total, CMDI‐evaluative scale, and CMDI‐vegetative scale were all highly significant, and reliable change indices reflected little change over time. In contrast, the correlation over time for the CMDI‐mood scale was significantly lower (p<0.05) than the CMDI‐evaluative and CMDI‐vegetative scale correlations, and over 40% of patients showed reliable change. Patients who improved in their mood showed increased use of active coping, while patients who worsened showed decreased active coping strategies; the latter were also significantly more likely to have been taking interferon beta drugs at both time points than patients who did not change in their mood functioning. CONCLUSIONS: Mood symptoms of depression are significantly more variable over time than neurovegetative or negative evaluative symptoms in MS patients. Decreased use of active coping strategies may put patients at risk of increased depressed mood, whereas increased use of active coping may result in decreased depressed mood longitudinally. Interferon beta use may put patients at risk of increases in depressed mood.